2021
DOI: 10.3389/fpsyg.2021.631531
|View full text |Cite
|
Sign up to set email alerts
|

Study of Effective Corridor Design to Improve Wayfinding in Underground Malls

Abstract: In retail space, wayfinding difficulties can cause problems, such as loss of time, stress, or discomfort, negatively affecting the shopping experience of consumers and even their patronage intentions. Although studies have reported that space configuration may facilitate navigation, there has been a lack of detailed discussion, particularly in underground malls, where people often encounter wayfinding issues. In this study, a series of exit-finding tasks in virtual malls were simulated to determine if it was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 38 publications
(81 reference statements)
3
11
0
Order By: Relevance
“…Respondents did not differentiate between medium and long corridors in this study; the crucial difference observed was that the shortest corridors were chosen more often. These results were expected and correspond to previous observations 43 . Also, the data persuasively demonstrate that respondents consider the presence of stairs in the corridor as a very strong cue for an evacuation route, since the likelihood of selecting a corridor with stairs was almost 10 times (or 15 times for the model with random slope terms for participants included) higher than selecting a corridor without stairs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Respondents did not differentiate between medium and long corridors in this study; the crucial difference observed was that the shortest corridors were chosen more often. These results were expected and correspond to previous observations 43 . Also, the data persuasively demonstrate that respondents consider the presence of stairs in the corridor as a very strong cue for an evacuation route, since the likelihood of selecting a corridor with stairs was almost 10 times (or 15 times for the model with random slope terms for participants included) higher than selecting a corridor without stairs.…”
Section: Discussionsupporting
confidence: 93%
“…When combining these factors, brightness increased the probability of choosing a wider corridor. Zhang and Park 43 studied the in uence of width, length, and height of corridors on the search for exits in underground malls, and also con rmed the wide corridor preference.…”
Section: Present Studymentioning
confidence: 99%
See 3 more Smart Citations